KOMPARASI KINERJA KEUANGAN SEBELUM DAN SESUDAH INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA - Dwirawati, Ni Made; Putu Wiagustini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024, 2024)
Initial Public Offering (IPO) is carried out by offering company shares to the public. The purpose of this study was to determine the differences in financial performance before and after the IPO of companies on the IDX using the Du Pont System method based on the ratios of NPM, TATO, ROI, EM, and ROE. The research population is companies that conducted an IPO on the IDX in 2017-2019 with a total of 148 companies and a total sample of 108 companies. Collecting data using non-participant observation with a sampling technique that is simple random sampling based on the Slovin formula. The method in this research is quantitative method and the type of research is descriptive comparative. Data analysis techniques were performed using a paired sample t-test with a significance level of 5%. The results of this study are that there is no significant difference in the company's financial performance after the IPO, where the values of NPM, TATO, ROI, EM, and ROE after the IPO have decreased. This means that the company's financial performance after the IPO shows unfavorable conditions. The research is expected to be able to provide additional information for companies and contribute to thinking in decision making related to differences in financial performance before and after the IPO.